Epidemiology of malocclusion and orthodontic treatment need of 12-13-year-old Malaysian schoolchildren - Esa, R.; Razak, I.A.; Allister, J.H. (2001)
Objective Data on malocclusion and orthodontic treatment need in Malaysia are limited. The purpose of thin study was to evaluate malocclusion and orthodontic treatment need in a sample of 12-13-year-old schoolchildren using the Dental Aesthetic Index (DAI), and to assess the relationship between malocclusion and socio-demographic variables, perceptions of need for orthodontic treatment, aesthetic perception and social functioning. Method The sampling procedure involved a multistage. clustered and stratified random sampling. The sample comprised of 1,519 schoolchildren attending 20 secondary government and government-aided schools in urban and rural areas of Klang District in Peninsular Malaysia. There were 772 males and 747 females. Each subject was administered a questionnaire eliciting standard demographic information such as gender, parents' income and ethnic origin and questions on perception of need for orthodontic treatment and satisfaction with dental appearance and function. Intra-oral examination for occlusal status using the DAI was performed for each subject. Results Most subjects (62.6) require no orthodontic treatment. Only about 7 had handicapping malocclusion that needed mandatory treatment. Malocclusion, as defined in this study, was found to be significantly associated with gender and subjects' area of residence. There were no significant differences in mean DAI scores for Malays, Chinese and Indian children. Significant associations a ere found between DAI scores and perception of need for orthodontic treatment, satisfaction with dental appearance and social functioning (P <0.01). Conclusion The findings will be useful for the public dental service to determine priority for orthodontic treatment as part of the comprehensive care provided by the School Dental Service (SDS).